(untitled) (Manarul Qur’an: Jurnal Ilmiah Studi Islam, 2022)
The leadership of the kiai in various aspects of the life of the santri and the community is fostered. The research seeks to reveal the role of KH Asy’ari’s leadership in placing Islamic education in Kalibeber Wonosobo, including the type of qualitative research, the character approach. Sources of interview data, documentation, and life records were analyzed descriptively with interpretative and synthetic steps. The research results: that the leadership model of KH. Asy’ari is charismatic, where his personal authority is evident in instilling confidence and being proactive in his subordinates. The steps he took in order to lay the roots of Islamic education, can be divided into two parts, first, directly where in practice he guides santri and santri bats in the knowledge of the yellow book, and the Koran. Second, indirectly, by making oneself a role model in various fields: including the struggle against the invaders, pioneers of waqf, fond of friendship, using banking services, productive agriculture, the establishment of NU in Wonosobo district. All of them are played with sincerity and wira’i so that they become a solid foundation and open the faucet of blessing for the next generation.